2020
DOI: 10.1016/j.amjsurg.2019.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of primary gastrointestinal stromal tumors (GISTs): Management and prognostic role of R1 resections

Abstract: Background: Surgery represents the best treatment for primary gastrointestinal stromal tumors (GISTs). The aim of this study is to analyse outcomes of surgical management in order to evaluate the influence of microscopically R1 margins on survival and recurrence in patients affected by GISTs. Methods: The study reviewed retrospective data from 74 patients surgically treated for primary GISTs without metastasis at diagnosis. Clinical and pathological findings, surgical procedures, information about follow up an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 33 publications
2
11
0
Order By: Relevance
“…Recently, several studies that including all GISTs reported that R1 resection did not negatively influence prognosis when excluded tumor rupture. 29–31 In the current study focused on rectal GISTs, we came to a similar result that the recurrence rates of R0 and R1 resection were not significantly different (18.8% vs 20.0%, p=1.000).…”
Section: Discussionsupporting
confidence: 68%
“…Recently, several studies that including all GISTs reported that R1 resection did not negatively influence prognosis when excluded tumor rupture. 29–31 In the current study focused on rectal GISTs, we came to a similar result that the recurrence rates of R0 and R1 resection were not significantly different (18.8% vs 20.0%, p=1.000).…”
Section: Discussionsupporting
confidence: 68%
“…Surgery is the main treatment for non-metastatic tumors performing a complete R0 resection of the tumor; however a retrospective study (Pantuso & al 2019) highlighted that positive microscopic margins R1 has no influence on the overall survival and the recurrence free survival, hence a R1 surgery can be fulfilling when R0 resection implies major functional consequences [ 10 ]. Since the arrival of tyrosine-kinase inhibitor with imatinib on the head of the list as adjuvant after surgery for moderate and high risk of recurrence or in neoadjuvant for non resectable or metastatic tumors has proven their efficiency with a gain of 13 months of median survival (Otani & al 2006) [ 11 ] and also the emerging of second line (Sunitinib) and third line (Regorafinib) therapies for resistant or intolerant GISTs validated in III phase studies [ 12 , 13 ], in 2014 coreless et al studied 645 patients ; 328 patients assigned to the placebo arm and 317 to the imatinib arm for 74 months concluding that genotype don’t interfere with recurrence free survival (RFS) but the size and site of the tumor along with mitotic rate influenced the RFS ; especially patients with KIT exon 11 deletion had a longer RFS after 1 year of imatinib [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Complete resection with microscopic negative margins (R0) and integrity of pseudocapsule is the main objective of surgery. Sometimes the achievement of disease-free resection margins requires major functional results, and in those cases it may be decided to perform a lesser aggressive surgical resection without obtaining negative margins in low-risk lesions [ 20 ]. Lymph nodes dissection is not recommended except when metastasis are clinically suspected.…”
Section: Discussionmentioning
confidence: 99%